Immediate moxifloxacin hypersensitivity: Is there more than currently meets the eye?. Issue 12 (26th July 2017) - Van Gasse, A. L.; Sabato, V.; Uyttebroek, A. P.; Elst, J.; Faber, M. A.; Hagendorens, M. M.; Mertens, C.; Bridts, C. H.; De Clerck, L. S.; Ebo, D. G.
Abstract: Immediate drug hypersensitivity reactions (IDHR) to moxifloxacin constitute a pathomechanistic conundrum and a diagnostic challenge. Our objective was to study whether simultaneous phenotyping and quantification of histamine release might add to our knowledge about the basophil activation properties of moxifloxacin and constitute a reliable diagnostic aid. Fifteen patients with an IDHR to moxifloxacin and nine moxifloxacin challenged controls were selected. All had a basophil activation test (BAT) with moxifloxacin. Flow cytometric analysis of basophil responses implied labeling for CD63, CD203c, and intracellular histamine. Unlike tolerant challenged controls, basophilic upregulation of CD203c in response to moxifloxacin was observed in seven of 15 patients. Only two of these seven patients demonstrated appearance of CD63 and release of histamine. In the remainder eight patients, no basophil responses were demonstrable. In conclusion, immediate hypersensitivity to moxifloxacin might involve mechanisms difficult to capture by traditional CD63‐/CD203c‐based BAT. Deciphering the complexity of quinolone IDHR seems mandatory.